AI Technology Training to Enhance English Language Teaching for English Teachers - Halimah, Nur; Saud, Indah Wardaty; Waris, Ahmad Mustamir; Saini, Fadhlan; Anuli, Wadan Y; Otoluwa, Moon Hidayati; Lovonita, Mohamad Adriansyah; Lahiking, Sri Nigshi (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
The rapid development of artificial intelligence (AI) has introduced new possibilities in education, particularly in English Language Teaching (ELT). This paper presents the outcomes of an AI-focused training program designed for English teachers at the elementary, junior high, and senior high school levels in Bitung City. The program aimed to enhance teachers’ understanding and practical ability in incorporating AI tools into both instructional and administrative tasks. This was a pilot program that involved 30 English teachers. The training employed the Asset-Based Community Development (ABCD) approach, which consisted of three key stages: (1) Identification of Community Potential and Strengths; (2) Development of the Assistance Program; and (3) Implementation of the Assistance Program. The findings indicate a notable improvement in the teachers' ability to utilize platforms such as ChatGPT, Gemini, and Wordwall, along with a boost in their confidence in adopting technology. Nonetheless, challenges such as inadequate infrastructure and limited post-training support remain significant obstacles. The study underscores the importance of ongoing and adaptable professional development to ensure the effective integration of AI into educational practices.